Information precision and return co-movements in private commercial real estate markets - Füss, Roland; Ruf, Daniel (Journal of Banking & Finance, 2022)
We test for return co-movements among international commercial real estate markets. Our spatial econometric model estimates the market exposure to the performance of a reference portfolio. This benchmark portfolio contains all markets with a higher level of transparency, which reveals valuable information about the pricing mechanism. Empirical evidence suggests that these indirect effects transmit from more transparent to less transparent markets. We then study the predictive power of different familiarity-based channels to overcome entry barriers by predicting returns in less transparent property markets. The evaluation of the prediction performance indicates that observed price signals in highly transparent markets are attributed to less transparent markets, which we interpret as informational herding.